THE EFFECTS OF LOW DOSES OF GAMMA RADIATION ON CELL SIZE PARAMETERS OF SOIL BACTERIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The changes of cell size parameters of Gram-negative Pseudomonas aeruginosa GRP3 and Gram-positive Bacillus subtilis AK3 soil bacteria during 30 min irradiation with low 7.2 mGy dose of Cs137 γ-rays with 2.56 μW·m−2·s−1 intensity were investigated. The obtained results have shown that the first 15 min irradiation was very stressful, and bacterial size parameters in both cases were increased, but during the next 15 min irradiation the size parameters were decreased approaching their initial values. Therefore, even though only very high doses of gamma radiation could be lethal for these bacteria, they are also sensitive to low doses. The results obtained allow to develop a new method for monitoring the level of radioactive contamination, based on membranous alterations in soil bacteria.
Keywords: gamma radiation, $ Bacillus$ $subtilis$ and $Pseudomonas$ $ aeruginosa$, cell size